(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The purpose of this piece is to shed light on the National Electronic Pharmacy Platform’s(NEPP) efforts to disseminate and promote the use of online pharmacies among Saudi people. Data from85 of the 225 NEPP-registered online pharmacies was analyzed for a cross-sectional quantitative study.Numerical analysis of the data was used to compile an extensive statistical profile of changing patternsin pharmaceutical use in Saudi Arabia. Despite NEPP’s relatively recent introduction (in 2023), there isclearly rising interest among pharmacies. There is a lot of room for expansion, and continued activitiesto raise consciousness and provide education will only help fuel that development. Africa’s increasingemphasis on pharmacy regulation and the proliferation of online drugstores underline the importance ofthe NEPP model for the continent’s individual nations. This research highlights the possible long-termimpact of NEPP on Saudi Arabia’s healthcare infrastructure. The increased rate at which antibacterialdrugs are prescribed is an important finding. This might mean that the Saudi population is seeing anincrease in bacterial illnesses, especially those related to breathing difficulties. It is crucial to treat theseinfections and raise awareness of antibacterial-related disorders. The Ministry of Health, the Saudi HealthService, the Pharmacy Council may use our findings as they formulate strategies to deal withantibacterial-related health issues.